Numerical and Experimental Study of the Temperature Distribution Characteristics of a Cryogenic Non-thermal Equilibrium Cylinder - Du Yicen; Cheng Ruijie; Wu Shize; Cai Aifeng; Wu Jingyi; Yang Guang (Zhileng xuebao, 2020)
To study the surface temperature distribution characteristics and related control methods of cryogenic non-thermal equilibrium cylinders under complex heat transfer conditions, this study establishes two models of heat transfer enhancement methods appended to pure top ventilation: an additional local nozzle air supply and a radiation screen. The temperature characteristics, such as radial temperature gradient, body temperature non-uniformity, and surface temperature non-uniformity of the cylinder, are analyzed by numerical simulation methods. The accuracy of the numerical simulation results was verified by experiments. On this basis, the influence of different heat transfer methods and operating parameters was quantitatively analyzed. The results show that, compared with simple top ventilation, the local nozzle air supply can increase the average temperature decrease of the cylinder by 5.1%, the temperature non-uniformity of the cylinder can be increased by 38.3%, and the temperature unevenness of the cylinder surface can be reduced. The temperature gradient of the cylinder was controlled on the side near the heat-conducting surface. With the addition of a cryogenic radiation screen, the coupled heat transfer of convection and radiation can reduce the average temperature decrease of the cylinder by 2.3%, increase the temperature unevenness of the cylinder by 57.5%, and reduce the temperature unevenness of the cylinder surface.